The Operator Selection Decision Support System Using The Simple Additive Method Weighting (SAW) At SPBU NO. 14. 205 Lubuk Pakam - Fadli Hermawan; R. Magdalena Simanjorang (DISTANCE: Journal of Data Science, Technology, and Computer Science, 2021)
The problems that occur at SPBU No.14.025 Lubuk Pakam are that there is no selection of the best operator that can serve consumers and the decisions are taken in the selection of operators are still subjective so that the decisions taken are not appropriate because they do not match the criteria as a reference in the selection of the operator. Therefore, this study used a decision support system that can be used to assist SPBU No. 14,025 Lubuk Pakam in determining the best operator in serving consumers. This decision support system will later be used in the selection of this gas station operator so that there are no problems in the future. For the selection of the best operator, four criteria are taken in the selection, namely the first there are ethical criteria, in this criterion related to attitudes and ways of speaking politely to superiors. Then the second discipline criterion in this criterion is related to the discipline of absenteeism or attendance and punctuality is given to each employee. The third criterion is the criteria in terms of caring or honesty, employees who have care or honesty each have a part of each job assigned to the employee, and the fourth is teamwork, this criterion is related to cohesiveness when working in collaboration with good at work and also help each other towards colleagues at work.